Bending and Compression Properties of ABS and PET Structural Materials Printed Using FDM Technology - Szczepanik, Stefan; Bednarczyk, Piotr (Journal of Casting & Materials Engineering, 2017)
The bend and compression mechanical properties of 3D-printed polyethylene terephthalate (PET) and acrylonitrile butadiene styrene (ABS) rectangular and cylindrical specimens (fully-dense and with circular, hexagonal, and rectangular perforations) are presented. In three-point bending, fully-dense PET flexural strength was 69 MPa, yield stress was 48.9 MPa, and yield stress from compression was 31.4 MPa. For ABS, these values were 59, 41.7, and 51.2 MPa, respectively – not significantly different from those of polymers manufactured by common techniques. Whereas perforation reduced density, the strength values were significantly lower, decreased for the circular perforation to a value of 20% strength for the fully-dense specimen. Specific strengths dropped quite significantly for the specimens tested in bending, whereas they did not differ significantly when tested by compression.